A History of Japanese Follow-up Surveys of Children Conceived through Artificial Insemination by Donor: The Evidence of "Superior" Children and Positive Eugenics. Issue 1 (2nd January 2022) - Yui, Hideki
Abstract: Artificial insemination by donor (AID) began in 1948 in Japan at Keio University. Due to criticism of this procedure, perhaps for the first time in the world, the university's obstetrics and gynecology researchers conducted follow-up surveys of children conceived through AID, showing the "superiority" of these children based on their mental development. This paper, by considering such surveys as evidence of children's "superiority" and positive eugenics, aims to clarify how such evidence was created and used. The survey reports were published in the medical journals from the late 1960s to the early 1980s, and obstetrics and gynecology researchers at the university referred to the survey results when writing articles for various media, including popular women's magazines, to promote AID. Eugenics started to lose its legitimacy from the 1970s due to the prevalence of movements for the disabled. After the 1990s, the "superiority" of the children was no longer claimed while the safety of assisted reproductive technology (ART) was being pursued to produce children who were "not inferior." This study concludes that, in the context of ART, physicians are adhering to the safety of the technology and prolonging the values of eugenics while dissociating from the pursuit of "superior" children.